Synergistic Effect of Mesenchymal Stem Cells and L-2-Oxothiazolidine-4-Carboxylate against P53/Caspase-3-Mediated Apoptosis in Lung Tissue of Rats Exposed to Chlorpyrifos - Nawal S. Hassan, Nora E.M. Shaheen, Marwa T. Hassen, Nawal Z. Haggag (Pakistan Journal of Medical & Health Sciences, 2022)
Chlorpyrifos [O, O-diethyl O-(3, 5, 6-trichloro-2-pyridinyl) phosphorothioate), which causes lung dysfunction, was used in this investigation to see if mesenchymal stem cells (MSCs) or l-2-oxothiazolidine-4-carboxylate (OTC) could alleviate the symptoms (CPF). Six sets of male albino rats (12010g) were formed. H2O was administered as a control, whereas OTC was administered orally at a dose of 100mg/kg b.wt./day and CPF was administered orally at a dose of 17.5mg/kg. It is possible to combine the use of one intravenous injection of MSCs (a single dose of 2106 cells) with the use of CPF+OTC, CPF+MSCS, or even CPF+MSCS+MSCS (CPF co-treated with OTC and MSCs). Results after a month demonstrated that treatment with OTC or/and MSCs improved GPx, MDA, and TAC in glutathione peroxidase (TAC). Lung tissue organisation was recovered by H&E after treatment with OTC and/or MSCs. As a result, it’s possible that OTC and MSCs work in concert to help protect lung tissue against the apoptotic effects of CPF.